Factors of venture capital investment activation - Telnova, H. V.; Petchenko, M. V.; Tkachenko, Serhii Oleksandrovych; Hurzhyi, Т.; Pyrohov, S. (Фінансово-кредитна діяльність: проблеми теорії і практики, 2022)
The relevance of the topic consists in the fact that due to limited start-up capital, high risk and uncertainty about profitability, lack of experience and, consequently, a positive credit history, venture capital is recognized as the main source of financing the development of many companies in the early stages. The purpose of the paper is to prove the hypothesis of the determining influence of fiscal factors of stimulation of research and development and a set of stable economic and political preconditions for expanding the presence of venture capital in the country. Based on the data of twenty European countries for 2007—2018 (240 observation points), a regression dependence of the amount of invested venture capital on tax preferences in research and development, research and development costs and country risk were constructed. The assessment of the parameters of the created regression model made it possible to prove that it can be used for forecasting volumes of investment of venture capital at the change of the factors of fiscal policy and reduction of macroeconomic risks. The directions of activation of venture financing for the countries are formed: for the development of high technologies and the implementation of innovative ideas, the state should apply tax benefits and preferences for research activities of small and medium enterprises; expansion is necessary for state support for innovation through the consolidation of state and local budgets on research programs, the creation of research and production clusters, technology incubators, support for individuals in their innovation initiatives; the high risk of the country not only leads to a decrease in the inflow of foreign venture capital: domestic investors will withdraw their venture capital and direct it to countries where the political and economic situation is more stable, which further deepens the economic shocks of the national economy and leads to political ones. The implementation of these measures will promote the development of high-tech enterprises, job creation in the country by overcoming the problem of limited financial resources through investment of venture capital.

Актуальність теми полягає у тому, що через обмеження стартового капіталу, високий ризик та невизначеність щодо прибутковості, відсутність досвіду роботи й, відповідно, позитивної кредитної історії, венчурний капітал визнається основним джерелом фінансування розвитку багатьох компаній на ранніх стадіях. Метою роботи визначено доведення гіпотези про визначальний вплив фіскальних факторів стимулювання наукових досліджень та розробок та сукупності стабільних економіко-політичних передумов на розширення присутності венчурного капіталу у країні. На підставі даних двадцяти країн Європи за 2007-2019 рр. (260 точок спостереження) побудовано регресійну залежність обсягів інвестованого венчурного капіталу від преференцій у оподаткуванні діяльності з наукових досліджень і розробок, обсягів витрат на наукові дослідження і розробки та від ризику країни. Оцінка параметрів побудованої регресійної моделі дозволила довести, що вона може бути використана для прогнозування обсягів інвестування венчурного капіталу під час зміни факторів фіскальної політики та зниження макроекономічних ризиків. Сформовано напрями активізації венчурного фінансування для країн: для розвитку високих технологій та впровадження інноваційних ідей державою мають застосовуватися податкові пільги та преференції для науково-дослідної діяльності суб’єктів малого та середнього підприємництва; розширення потребує державна підтримка інноваційної діяльності через консолідацію коштів державного та місцевих бюджетів на програмах наукової діяльності, створенні науково-виробничих кластерів, технологічних інкубаторів, підтримки фізичних осіб у їх інноваційних ініціативах; високий ризик країни не тільки обумовлює зниження притоку іноземного венчурного капіталу: внутрішні інвестори за цієї умови будуть виводити свій венчурний капітал у країни, де більш стабільна політична та економічна ситуація, що ще більше поглиблює економічні шоки національної економіки та призводить до виникнення політичних. Реалізація комплексу означених заходів сприятиме розвитку високотехнологічних підприємств, створенні робочих місць у країні через подолання проблеми обмежених фінансових ресурсів за допомогою інвестування венчурного капіталу.
Keywords: venture capital; factor; fiscal policy; risk; model; венчурний капітал; фактор; фіскальна політика; ризик; модель